Is there any truth in the myth that IVF treatments involve weight gain? - Saar-Ryss, Bozhena; Shilo, Michael; Friger, Michael; Grin, Leonti; Michailov, Yulia; Meltcer, Simion; Zaks, Svetlana; Rabinson, Jacob; Lazer, Tal; Friedler, Shevach (Frontiers in Reproductive Health, 2024)
Purpose To examine body weight change in women undergoing in vitro fertilization and embryo transfer (IVF-ET) using antagonist protocol after up to three treatment cycles. Methods A prospective cohort study among IVF patients treated between 2018 and 2019. Each patient underwent weight measurement three times during the treatment cycle: before treatment, at the beginning of the hormonal stimulation, and at the completion of the cycle, on the day of the pregnancy test. Data were also analyzed according to the body mass index (BMI) groups for normal weight, overweight, and obese patients. Finally, weight changes were recorded following altogether 519 treatment cycles, 240, 131, and 148 cycles, for normal weight, overweight, and obese patients, respectively. Results The change in the patient's weight was clinically non-significant either during the waiting period or during gonadotropin administration, and overall, during the first, second, or third treatment cycles. The recorded mean total weight change of 0.26 ± 1.85, 0.4 ± 1.81, and 0.17 ± 1.7, after the first, second, or third treatment cycles, represent a change of 0.36%, 0.56%, and 0.23% of their initial weights, respectively. This change of less than 1% of the body weight falls short of the clinically significant weight gain of 5%–7%. Analyzing the data for the various BMI groups, the changes observed in body weight were under 1%, hence with no clinical significance. Conclusion The findings of the study reject the myth that hormone therapy involves clinically significant weight gain, and this can lower the concerns of many patients who are candidates for treatment of assisted reproductive technology.